Valorization of Red Beetweed "Beta Vulgaris L." From The Vakinankaratra Region in Wine in Circular Economy With Zero Waste - Robijaona Rahelivololoniaina B.; Elisoamiadana P. (Britain International of Exact Sciences (BIoEx) Journal, 2024)
Beet (Beta vulgaris L.) is a vegetable, but its sweet taste prompted us to explore its use in wine-making. After TXRF analysis and phytochemical screening, the richness in micronutrients and chemical families of its pulp and peel led to the use of whole beet in the winemaking process. The temperature observed in each trial is well within the temperature range for red winemaking (22.0°C- 28.8°C). the pH decreases as a function of fermentation time, due to ethanol production and the consumption of part of the malic acid by the yeasts. The pH of musts and wines is generally between 3 and 4. The conversion of sugar is not total for all the trials but we can say that the fermentation is accelerating. There is still a small sugar-to-alcohol conversion scale equal to 0.2%. During the fermentation, the alcoholic strength depends on the type of hydrolysis used and the rate of glucose release. The values of the total acidity in H2SO4 were found to range from 3.867 to 4.586. According to the results of the analyses carried out, the physico-chemical characteristics of the beet wine comply with European regulations. The vinasse was recycled and underwent a composting process. The C/N ratio (15.16), P (0.95%), Ca (3.05%), Mg (2.25%), K (5.16%) and Na (0.24%) contents were determined. The vinasse compost was used to prepare a beet nursery, and then allowed the young plants from the nursery to grow normally. Beet farming in a zero-waste circular economy.